2021
DOI: 10.3390/app11125471
|View full text |Cite
|
Sign up to set email alerts
|

Laminar-Turbulent Transition Localization in Thermographic Flow Visualization by Means of Principal Component Analysis

Abstract: Thermographic flow visualization is a contactless, non-invasive technique to visualize the boundary layer flow on wind turbine rotor blades, to assess the aerodynamic condition and consequently the efficiency of the entire wind turbine. In applications on wind turbines in operation, the distinguishability between the laminar and turbulent flow regime cannot be easily increased artificially and solely depends on the energy input from the sun. State-of-the-art image processing methods are able to increase the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Dollinger et al [15] demonstrated how temporal standard deviation or Fourier coefficient amplitude from 30 images can enhance the SNR for studying wind turbine blades. For the same application Gleichauf et al [16] applied principle component analysis on up to 10 000 images, showing improved robustness compared to using an averaging or standard deviation.…”
Section: Enhanced Post-processing Methodsmentioning
confidence: 99%
“…Dollinger et al [15] demonstrated how temporal standard deviation or Fourier coefficient amplitude from 30 images can enhance the SNR for studying wind turbine blades. For the same application Gleichauf et al [16] applied principle component analysis on up to 10 000 images, showing improved robustness compared to using an averaging or standard deviation.…”
Section: Enhanced Post-processing Methodsmentioning
confidence: 99%
“…Hence, PCA allows to separate the desired flow information from the non-desired image information or interference. In measurements with low contrast, the method was able to significantly increase the distinguishability and reduce the measurement error of the flow transition localization [7].…”
Section: Objectivesmentioning
confidence: 99%
“…Using IRT on wind turbines, the CNR of the thermographic images is limited due to the field conditions (for instance low solar radiation) or a small sensitivity of the measurement effect (as seen in the detection of static [14] or dynamic stall [15], or when using smallsignal evaluation approaches such as differential images tested on an airfoil [16] and rotor blades of wind turbines [17]). Gleichauf et al improved the contrast with averaging methods, i.e., non negative Matrix factorization [18] and principle component analysis [19]. Nevertheless, without including previous knowledge, the available CNR directly limits the achievable measurement uncertainty for the determination of the laminar-turbulent transition position on the rotor blade of a wind turbine.…”
Section: State Of the Artmentioning
confidence: 99%